2009 IEEE/PES Power Systems Conference and Exposition 2009
DOI: 10.1109/psce.2009.4840133
|View full text |Cite
|
Sign up to set email alerts
|

Wind power day-ahead uncertainty management through stochastic unit commitment policies

Abstract: Day-ahead uncertainty management in power systems has traditionally been approached by means of multistage decision making and operating reserve requirements. An alternate approach for managing uncertainty is a stochastic formulation,which allows the explicit modeling of the sources of uncertainty. The large investments in wind power has increased the importance of operations uncertainty management due to the considerable operational uncertainty wind plants have. This paper evaluates the benefits of a combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 12 publications
0
56
2
Order By: Relevance
“…3 surplus (cost in case of inelastic demands) in intra-day operations. Examples include the works of Takriti et al (1996), Wang et al (2008), Constantinescu et al (2011), Jin et al (2014), Ruiz et al (2009), Bouffard et al (2005), Papavasiliou and Oren (2013). These studies have demonstrated significant improvements in reliability over deterministic formulations.…”
Section: Previous Workmentioning
confidence: 99%
“…3 surplus (cost in case of inelastic demands) in intra-day operations. Examples include the works of Takriti et al (1996), Wang et al (2008), Constantinescu et al (2011), Jin et al (2014), Ruiz et al (2009), Bouffard et al (2005), Papavasiliou and Oren (2013). These studies have demonstrated significant improvements in reliability over deterministic formulations.…”
Section: Previous Workmentioning
confidence: 99%
“…The technical literature presents methods for WP bidding strategies solving using different approaches: the first one is the use of WP with technologies of storage of energy [18]; the use of economic options as a tool for WPP to hedge against WP Uncer [19]; another approach is the design of Stoc models in order to obtain OBS for WPP participating in an EMar [20], without the aforementioned policies. The 3rd line of action is a Stoc formulation explicitly modelling the Uncer faced by a WPP [21], using indeterminate measures and an established of scenarios built by WP forecast and market-clearing EPr forecast [22] requests.…”
Section: State Of the Artmentioning
confidence: 99%
“…The stochastic model is a formulation explicitly taking into account the uncertainties tackled by the ScP of a WiPP [19], using multiple scenarios obtained by computer applications for wind power and market price forecasts [20].…”
Section: State Of the Artmentioning
confidence: 99%
“…In (18), the minimum DX will be satisfied for all the sets of sequential periods of size r DX . In (19), the minimum DX will be satisfied for the last The total power produced by the ThU is stated as:…”
Section: Thermal Power Producermentioning
confidence: 99%